2017
DOI: 10.24251/hicss.2017.552
|View full text |Cite
|
Sign up to set email alerts
|

How Individual Technology Propensities and Organizational Culture Influence B2B Customers Behavioral Intention to Use Digital Services at Work?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The influence of technology readiness (and its' dimensions) on technology usage intention has been acknowledged in previous literature (Pham et al, 2020;Blut & Wang, 2019;Prodanova et al, 2018;El Alfy et al, 2017;Hallikainen et al, 2017;Mummalaneni et al, 2016;Hwang & Good, 2014). Therefore, it can be implied that the TR concepts proposed by Parasuraman (2000) were capable to serve as an important determinant towards online purchase intention.…”
Section: Proposed Technology Readiness Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…The influence of technology readiness (and its' dimensions) on technology usage intention has been acknowledged in previous literature (Pham et al, 2020;Blut & Wang, 2019;Prodanova et al, 2018;El Alfy et al, 2017;Hallikainen et al, 2017;Mummalaneni et al, 2016;Hwang & Good, 2014). Therefore, it can be implied that the TR concepts proposed by Parasuraman (2000) were capable to serve as an important determinant towards online purchase intention.…”
Section: Proposed Technology Readiness Modelmentioning
confidence: 92%
“…On the other hand, when being examined from the multidimensional perspective, TR was also found to have a strong prediction strength towards technology usage intention. For instance, the motivators dimension of TR (optimism and innovativeness) was found to have a positive influence on technology usage intention Hallikainen et al, 2017;Hwang & Good, 2014). Furthermore, the inhibitor dimension of TR (discomfort and insecurity) was identified to have a negative relationship with technology usage intention (Pham et al, 2020;Hallikainen et al, 2017;Hwang & Good, 2014).…”
Section: Proposed Technology Readiness Modelmentioning
confidence: 96%
“…Findings shows that emotional towards intention to complain, Strizhakova and Tsarenko (2017); emotional intelligence and emotional labour, Kim and Park (2016); emotional intelligence and communication competence, Kang and Kim, (2016); workplace bully and emotional intelligence, Kim and Park (2016); studies are towards turnover intention. In conclusion, research in emotional intelligence and job performance has found a significant relationship between them Vratsikh et al 2016; Deshwal (2016); Sony and Mekoth (2015); Yoke and Panatik (2015) Various studies were conducted on antecedents of intention such as management support and behavioral intention toward using digital (Hallikainen, Paesbrugghe, Laukkanen, Rangarajan, & Gabrielsson, 2017), work-life balance and intention to leave (Khairunneezam, 2011), conflict relationship and job burnout towards turnover intention (Shaukat, Yousaf, & Sanders, 2017), empowerment and turnover intention (Kim & Fernandez, 2017),transformational leadership and turnover intention (Ariyabuddhiphongs & Kahn, 2017), job or job support towards turnover intention of non-profit employees (Knapp, Smith, & Sprinkle, 2017), Lee and Chelladurai (2018) on emotional intelligence and turnover intention, as moderator in intention to leave (Pradhan & Jena, 2018), emotional intelligence and entrepreneurial intention (Miao, Humphrey, Qian, & Pollack, 2018) and emotional intelligence and career intentions (Walters, 2018). But emotional intelligence and performance has been studied in various relationship or association but studies on emotional intelligence and intention to perform was never explored, leaving a gap in it (Raman et al, 2020).…”
Section: Emotional Intelligence and Intention To Performmentioning
confidence: 97%
“…In addition, various studies have been conducted related to intention such as supervisor relationship and work engagement towards intent to quit by Rodwell. William and Gulyas (2017) and the study of management support towards employee"s intention to turnover by (Hallikainen, Paesbrugghe, Laukkanen, Rangarajan and Gabrielsson 2017). Intention to quit among academic staff in public universities (Khairunneezam, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated the role of OC on absorptive capacity and IT success [14], IT adoption and diffusion [7], IT implementation [13], and user computer efficacy [30]. Recently, OC has been discussed to be an enabler for new knowledge and trigger for creativity [25], but also an obstacle regarding the adoption of new digital services [12].…”
Section: Introductionmentioning
confidence: 99%